Fenomena komunikasi wanita karir sebagai top manajemen di Pertamina Hulu Rokan (studi fenomenologi komunikasi pada top management wanita di pertamina hulu rokan) - Diana, Nova; Firdaus, Muhammad; Yozani, Ringgo Eldapi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research analyzes the communication experiences of women in top management positions at PT. Pertamina Hulu Rokan (PHR), with a focus on the role of communication, challenges and its impact on the organization. Using a phenomenological approach, this research explores the motives behind career women's decisions, namely parental encouragement, determination, opportunity, as well as proof, economics and social status. The research results show that women's interpretation of leaders includes aspects of being nurturing, wise, and inspiring, with self-concepts divided into three categories: tough, ambitious, and friendly. Their communication experiences are divided into two categories, namely pleasant communication obtained from family, community and work support, and unpleasant communication due to busyness which reduces time with family. This research provides insight into the contribution of women in leadership in the oil and gas sector and the importance of effective and collaborative communication in facing challenges..